Evaluation of mefenamic acid mutual prodrugs - Shah K.; Shrivastava S.K.; Mishra P. (My University, 2025)
Mutual prodrugs consisting of mefenamic acid with menthol and thymol have been synthesized as a gastrosparing NSAIDs, devoid of ulcerogenic side effects. The structures of synthesized esters were confirmed by IR, 1H NMR, and mass spectroscopy. The kinetics of ester hydrolysis was studied in nonenzymatic buffer solutions, at pH 2 and 7.4 as well as in human plasma by HPLC. Its anti-inflammatory, analgesic, and ulcerogenic activities were evaluated. Then biochemical parameters (GWM and Hexosamine), oxidative parameters (LPO, GSH, CAT, and SOD), and protein estimation was also done. The results indicated that synthesized prodrugs are chemically stable, biolabile, and posses optimum lipophilicity. The synthesized prodrugs are characterized by better ulcer index than the parent drug. © 2012 Springer Science+Business Media, LLC.